The negative and positive impact of modern technology and modern science on human life and health - Martynenko, Nataliia; Elsayed, Mohammed (Kharkiv National Medical University, 2019)
Authors of publication deal with the advantages and disadvantages of modern technologies in their influence on the life and health of population.
Keywords: global warfare; era of industrial revolution; a smart TV; technology; smart phones; screen dependency disorder; gadget-dependent children